2018
DOI: 10.1177/1069072718763636
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Validation of the Turkish Version of the Decent Work Scale

Abstract: This study examined the psychometric properties of the Turkish version of the Decent Work Scale (DWS), a recently developed measure that assesses the psychological experience of the quality of one’s work life. The proposed five-factor structure was verified with a sample of 326 Turkish working adults. Consistent with previous research, a five-factor bifactor model showed best fit to the data. The results of multigroup confirmatory factor analysis showed that the structure of the instrument was invariant across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 60 publications
4
27
1
2
Order By: Relevance
“…Although we view decent work as a key predecessor of meaningful work, some individuals may have the capacity to experience their work as meaningful even if it is not decent. For example, correlations between decent work and meaningful work are strong but range from 0.48-0.58 (Allan, Tebbe, Bouchard, & Duffy, 2018;Duffy et al, 2017;Işık, Kozan, & Işık, 2018), indicating these are not completely overlapping constructsit is possible to have one without the other. To date, however, it is unclear what types of individuals would be more likely to experience meaningful work in environments where one or more components of decent work is absent.…”
Section: Access To Decent Workmentioning
confidence: 99%
“…Although we view decent work as a key predecessor of meaningful work, some individuals may have the capacity to experience their work as meaningful even if it is not decent. For example, correlations between decent work and meaningful work are strong but range from 0.48-0.58 (Allan, Tebbe, Bouchard, & Duffy, 2018;Duffy et al, 2017;Işık, Kozan, & Işık, 2018), indicating these are not completely overlapping constructsit is possible to have one without the other. To date, however, it is unclear what types of individuals would be more likely to experience meaningful work in environments where one or more components of decent work is absent.…”
Section: Access To Decent Workmentioning
confidence: 99%
“…The PWT also includes several proposed moderators including proactive personality, CC, social support, and economic conditions, which are thought to be modifiable and to influence the relations between the macro-level factors, mediators (work volition and career adaptability), and the attainment of decent work. Initial research using the PWT has produced promising results, including empirical support for many aspects of the theoretical model (e.g., Allan, Tebbe, Bouchard, & Duffy, 2018; Autin, Douglass, Duffy, England, & Allan, 2017; Douglass, Velez, Conlin, Duffy, & England, 2017; Tokar & Kaut, 2018) and the development of a self-report measure of decent work (Duffy et al, 2017; Işık, Kozan, & Isik, 2018). The PWT offers flexibility in defining specific constructs in ways that are consistent with a broad scholarly agenda.…”
Section: Social Justice and Work/career: The Psychology Of Working Momentioning
confidence: 99%
“…Initially forged from activists and scholars in labor movements, public policy, and economics (ILO, 2008; Standing, 2014), the Decent Work Agenda has largely marginalized a critical aspect of people’s work lives—their psychological experience and meaning in relation to work. As a response to this notable gap in knowledge and public policy, psychologists have recently begun to focus theoretical and research attention to the problem of decent work (e.g., Blustein, Olle, Connors-Kellgren, & Diamonti, 2016; Di Fabio & Blustein, 2016; Di Fabio & Maree, 2016; Duffy et al, 2016, 2017; Isik et al, 2018; Pouyaud, 2016). Building on a social philosophical critique by Deranty and MacMillan (2012), which proposed that the ILO concept of decent work focuses too heavily on the social and economic aspects of work, Blustein, Olle, Connors-Kellgren, and Diamonti (2016) adopted an explicitly psychological perspective to critique the existing macro-level lens with which decent work has been defined and operationalized.…”
Section: A Psychological Approach To Decent Workmentioning
confidence: 99%
“…We used the 15-item, five subscale DWS to assess perceptions of decent work, defined as work that possesses the following five components: (1) interpersonally and physically safe working environments, (2) health-care benefits, (3) compensation that is adequate, (4) hours that allow one to engage in free time and rest, and (5) organizational values that allow a work–life balance (Duffy et al, 2017). Aligned with previous research, we summed the five Decent Work subscales, with higher scores on the scale indicated greater levels of decent work (Autin et al, 2019; Duffy et al, 2017; Işık, Kozan, & Işık, 2018; Kozan, Işık, & Blustein, 2019). Example items included “I feel physically safe interacting with people at work” and “I get good health-care benefits from my job,” where participants indicated their agreement on a 7-point Likert-type scale where 1 = strongly disagree and 7 = strongly agree .…”
Section: Methodsmentioning
confidence: 99%